Detection and assessment of special needs in school (Journal of Parents and Teachers, 2013)
A large number of students have difficulties  to progress academically. Only those with intellectual disabilities; sensory; motor ; or developmental disorders can be considered students with special educational needs .The contributions of neuropsychology allow a better understanding of special needs; understanding the origin and evolution of which is the result of the interaction of biological ( genetic; brain dysfunction ) and education (family; school ) .At school age; brain of students is  in process of growing; maturation and neural network configuration; so that the difficulties are often not specific and affect various dimensions of development.Early detection is essential to implement as soon as possible intervention programs and take advantage of increased brain plasticity.The psychoeducational assessment as assessment and identification process of special needs must consider the student's performance in the different dimensions of development as the school and family context. In this process; coordination between the counselor; teachers and family is essential.
Keywords: Special educational needs; brain; early detection; psychoeducational assessment; Family and disabilities